PARTNERSHIP WITH LOCAL COMMUNITY IN SCHOOL CURRICULUM FOR ENCOURAGING ENTREPRENEURIAL COMPETENCE (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
Distinctiveness of an individual school is reflected in the school curriculum which is used to organize educational activities. The purpose of the paper is to give theoretical and legislative frame as well as the results of the analysis of three primary and three secondary school curricula. Document analysis is used as a research method. The basic areas of school curriculum are school efficiency, process of learning and teaching, school management, teacher’s professionalism and strategies of quality development. Each school constructs its own curriculum which is aligned with its optimal possibilities and demands of the national curriculum. A school curriculum plans for coexistence between students, teachers, parents, school management and local community. School and local community partnership encourages development of entrepreneurial competences, so it is necessary for cultural, economic and social events, in the context of pedagogical values, to find their place in the school. The analysis of legislation shows the need of introducing and developing entrepreneurial competences in schools, while the review of relevant research shows that 76. 2 % of teachers consider that entrepreneurial competences should be introduced in schools (Jokić et al., 2007). Entrepreneurial competences are developed in the school curriculum through cooperation with the local community. The analysis of school curricula points out the need of increasing the number of activities suggested in the school curricula (extracurricular activities, projects, etc.).Keywords: Schools, school curriculum, entrepreneurship, cooperation, local community